Design and evaluation of an immunology and pathology course that is tailored to today’s dentistry students - de Vries, Teun J.; Schoenmaker, Ton; Peferoen, Laura A. N.; Krom, Bastiaan P.; Bloemena, Elisabeth (Frontiers in Oral Health, 2024)
Curricular reform provides new opportunities to renovate important pillars of the dentistry curriculum, such as immunology and pathology, with novel approaches that appeal to new generations of students. When redesigning a course that integrates both immunology and pathology at the level that provides dentistry students with sustainable knowledge that is useful for their entire career, several challenges must be met. The objective of the study is to describe the considerations involved in the design phase of such a new course. Firstly, the course should be compatible with the new view on the incorporation of more active learning and teaching methods. Practically, this means that the course design should contain fewer lectures and more s¬¬¬¬eminars and tutorials, where the students have fewer contact hours and actively engage in using recently acquired knowledge within a contextual background. A mandatory session of team-based learning provides opportunities to apply knowledge in combination with academic reasoning skills, teamwork and communication. Second, for a four-week course, choices must be made: students will not become immunologists nor pathologists in such a short period. A governing principle for this course’s design is that it should be based on understanding the basic principles of immunology and pathology. The ultimate goal for the students is to make the course immuno-logical and patho-logical, challenging them to reach a next level but clearly without oversimplification. Part of the course design should allow room for students to further study an immunological topic of their own choice, thereby contributing to their immunological curiosity and to their academic development. Thirdly, to make it tailored to a new generation of dentists, examples from the field of dentistry are actively integrated in all aspects of the course. Finally, the era of ChatGPT provides novel opportunities to use generative AI tools in the learning process, but it demands critical thinking of how to use it in a newly designed course. A mid-course evaluation revealed that students acknowledged that immunology and pathology were presented as an integrated course. These methods proved to be appropriate and logical choices for reaching the learning goals of the course.